Dangerous Pollutants (Xenobiotics) in Urban Water Cycle - Hlavinek, Petr.; Bonacci, Ongjen; Marsalek, Jiri.; Mahrikova, Ivana; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2008)
The topics focused on evaluation of impact of xenobiotics in the whole Urban Water Cycle are an interdisciplinary task which has a rising concern these days. Xenobiotics includes both inorganic elements like heavy metals, metalloids and man-made organic compounds such as pesticides, surfactants, solvents, fragrances, flavours, and pharmaceuticals as well as endocrine disrupters. It has been estimated that 70,000 xenobiotics may potentially be hazardous for humans and/or ecosystems. Water supply, urban drainage and wastewater treatment systems were originally designed to solve just conventional problems such as supply of potable water, flooding prevention and sanitation. The main problem within the conventional urban water cycle approaches is absence of design to deal with xenobiotics. Nowadays can be seen increased focus on rainwater use, wastewater reclamation and reuse in industrial and as well in domestic sector what increase the exposure to xenobiotics. Innovative approaches are therefore needed to prevent xenobiotics from being discharged into surface waters where they may give rise to impacts on the chemical water quality and ecological status of receiving waters as it is already recognized by the EU-Water Framework Directive. Under such circumstances it is needed to assess knowledge gaps within the integrated water management with a particular emphasis on xenobiotics. Leaking sewer pipes, land application of treatment residues and increased focus on soil-infiltration of stormwater and wastewater further put the urban and peri-urban soil and groundwater resources at a potential risk that only rudimentary is accessed now. The integrated nature of the urban water systems and the ability of xenobiotics to spread across structural boundaries and into the environment where ecological systems and humans are exposed calls for an intersectorial and multidisciplinary approach to problem awareness and solution. Pollutants of interest have mainly been the conventional parameters (BOD, COD, N, P, SS and micro-organisms). Thus, there is a need to understand the sources, flow paths, fate (transport, treatment, natural attenuation) and impact of xenobiotics on both humans and environment in this technical system. This book is based on the discussions and papers prepared for the NATO Advanced Research Workshop that took place in Velke Bilovice (Lednice area), Czech Republic under the auspices of the NATO Security Through Science Programme and addressed urban water management problems. The main purpose of the workshop was to critically assess the existing knowledge on Xenobiotics in urban water cycle, with respect to diverse conditions in participating countries, and promote close co-operation among scientists with different professional experience from different countries. The ARW technical program comprised papers on 4 topics, Challenges in Water Resources Management, Safety and Security of Water Supply and Sanitation, Xenobiotics and its treatment, Impact assessment and Wastewater Treatment and Reuse.
Preface -- Acknowledgement -- Challenges In Water Resources Management -- A Whole-Life Cost Approach To Sewerage And Potable Water System Management -- Reuse Of Urban Water: Impact Of Product Choice -- Urban Water Resources Management In Romania - Perspectives For The Sustainable Development In Order To Supply Water To Human Settlements -- Water Quality And Wastewater Treatment Systems In Georgia -- Stormwater Management In Urbanised Areas -- Safety And Security Of Water Supply And Sanitation -- Small Urban Rivers Of Chernivtsi: Level Of Organic Pollutants Content, Main Sources And Effective Green Solutions -- Reconstruction And Rehabilitation Of Sewer Systems In Slovakia -- Waste Water Treatment From Small Urban Areas -- Allium-Assay In Evaluation Of Drinking And Surface Water Mutagenicity -- Modelling Water Quality For Integrated Water Resources Management At The Basin Scale -- Xenobiotics And Its Treatment, Impact Assessment -- Polar Organic Micropollutants In The Water Cycle -- Pharmaceuticals And Personal Care Products (Ppcp) In Canadian Urban Waters: A Management Perspective -- Viruses In Ground Water -- Ecohydrology Of Dojran Lake -- Polychlorinated Biphenyls In Urban Environment Of Belarus: Sources, Pollution, Problems Of Monitoring -- Phytotoxicity Assessment Of Various Effluent Waters, Surface Water And Sediments -- Monitoring And Modelling Pesticide Dynamics In Surface Water -- Methods For Toxicity Testing Of Xenobiotics In Wastewater Treatment Plants And In Receiving Water Bodies -- Chromium And Atrazine Contamination Of The Ljubljansko Polje Aquifer -- Wastewater Treatment And Reuse; Cost Modelling In Waste Water Treatment Processes: An Empirical Analysis For Spain -- Review On The Assessment Of The Removal Efficiency Of Wastewater Treatment Plants For Selected Xenobiotics -- Poster Section -- Aqueous Photocatalysis, Natural Organic Matter Characterization And Removal: A Case Study Of The Photacatalytic Oxidation Of Fulvic Acid -- Chemical And Ecological Problems Of Small Reservoirs At Designing Of Wastewater Treatment Installations -- Facts, Contradictions And Possible Improvement Actions For Hazardous Wastewater Management - A Case Study -- Complex Kinetic Indexes For Estimation Of Surface And Waste Water Quality -- Continually Measured Orp And Ph Signal For Control Of Nitrogen Removal -- Operation Of Domestic Wastewater Treatment Plant With Submerged Membrane Modules -- The Comparative Study Of The Overall Effect Of Crude Oil On Fish In Early Stages Of Development -- Evaluation Of Vilnius City (Lithuania) Snow Pollution Toxicity By Use Of Fish Biotests -- Minimization Of Dangerous Pollutants In The New Sanitation Concept For Separation Treatment Of Wastewater -- Pollution Of Ground Sources Of Drinking Water With Technogenic Tritium -- Subject Index.
Keywords: ENVIRONMENTAL SCIENCES; CIVIL ENGINEERING; ENVIRONMENTAL TOXICOLOGY; ENVIRONMENTAL POLLUTION; ENVIRONMENT; WASTE WATER TECHNOLOGY / WATER POLLUTION CONTROL / WATER MANAGEMENT / AQUATIC POLLUTION; ECOTOXICOLOGY; CIVIL ENGINEERING